Formulation And In-Vitro Evaluation Of Floating Pulsatile Beads Of Indomethacin For Site And Time-Specific Release - Sudhamani, T.; Radhakrishnan, M. (Asian Journal of Pharmaceutical Research and Development, 2013)
The objective of this work was to develop site and time specific oral floating pulsatile multiparticulate system of indomethacin intended for chronotherapy. This was achieved by formulation of beads with blend of floating and pulsatile principles showed typical two phase release profile with a lag time in acidic stomach pH correlated well with floating time followed by rapid release only in small intestine pH and which was designed by formulation of water insoluble complexes of calcium pectinate with drug. The formulated beads were evaluated for bulk density, particle size, percentage encapsulation, buoyancy and in-vitro release studies. The floating pulsatile beads obtained were decreased bulk density below one and provided higher percentage of encapsulation. All beads showed good buoyancy as 4 to 6 hours of lag time in stomach pH followed by rapid pulse release in small intestine pH made suite for site and time-specific pulsatile release of drug.